1987
DOI: 10.1007/bf00441603
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cyproterone acetate on the growth of children with central precocious puberty

Abstract: We have examined the growth and skeletal maturation of 19 children (6 male, 13 female) with central precocious puberty. The aetiology in nine patients (5 male, 4 female) was secondary to a hypothalamic hamartoma. Six children (2 male, 4 female) received no treatment whereas 13 children (4 male, 9 female) were treated with cyproterone acetate in a mean dose of 68 mg/m2 per day (range, 34-260) for a mean duration of 4.5 years (range, 0.8-7.9). There was no significant difference between height SDS for bone age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Before the development of the GnRHan, children with CPP had a significantly compromised final height prognosis because of rapid epiphyseal maturation and fusion. Various medications to suppress the secretion of the sex steroids in CPP such as medroxyprogesterone and cyproterone acetate were tried over the years, but they did not alter the height prognosis of children with CPP 23–25. Although the physical signs of CPP are suppressed with these medications, no difference in growth and bone age advancement was noted between children treated with medroxyprogester‐one and cypoterone acetate and those left untreated.…”
Section: Predicted Height (Ph) In Children With Central Precocious Pumentioning
confidence: 99%
“…Before the development of the GnRHan, children with CPP had a significantly compromised final height prognosis because of rapid epiphyseal maturation and fusion. Various medications to suppress the secretion of the sex steroids in CPP such as medroxyprogesterone and cyproterone acetate were tried over the years, but they did not alter the height prognosis of children with CPP 23–25. Although the physical signs of CPP are suppressed with these medications, no difference in growth and bone age advancement was noted between children treated with medroxyprogester‐one and cypoterone acetate and those left untreated.…”
Section: Predicted Height (Ph) In Children With Central Precocious Pumentioning
confidence: 99%
“…The natural history of the growth prognosis of central precocious puberty was described in 1974 (18). In this section, the discussion will be confined to girls, as central precocious puberty is more common in girls and also because the older literature on untreated boys with (19,20), though it was appreciated in North America that medroxyprogesterone did not affect height prognosis. When treatment with G n R H analogues, which have a specific action on the gonadotroph, was introduced, it was hoped that they would improve height prognosis.…”
Section: Gnrh Analogues and Growth In Central Precocious Pubertymentioning
confidence: 99%
“…This naturally led to the proposal that such analogues could be used in treatment to retard precocious puberty. Indeed, such trials have been reported in various publications (19)(20)(21)(22). However, although these publications note the spectacular results in the control of gonadal or gonadotrophin secretion, the effect on growth and bone maturation remains unclear because of the lack of follow-up of this type of treatment.…”
Section: Effect Of Growth Retarding Treatmentsmentioning
confidence: 99%
“…It is generally accepted that CPA is effective for the arrest of the development of secondary sexual characteristics. However, there has been considerable controversy about the effect on improvement in stature [11,17,18,201 .…”
Section: Introductionmentioning
confidence: 99%